NTP i lichnost' [ NTP: nauchno-tekhnicheskii progress ] . NTP i lichnost' [ NTP: nauchno-tekhnicheskii progress ] . Scientific and Technological Development and Personality . НТП и личность [ НТП: научно-технический прогресс ] - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Problems of interaction: society, state, and personality. Featured in the program: Rekemchuk, Aleksandr Evseevich (Writer) Contributors: Glavnaia redaktsiia propagandy (Studio) Проблемы взаимодействия: общество, государство и личность. В программе участвуют: Рекемчук, Александр Евсеевич (Писатель) Создатели: Главная редакция пропаганды (Студия)